A simple methodology for predicting process-induced spring-in of curved composite parts. (June 2022) - Xu, Mi; Zhou, Rui; Ni, Aiqing; Ding, Anxin
Abstract: A simple methodology for predicting spring-in of curved composite parts just inputting the properties of constituent materials in rubbery and glassy states is proposed here, which contains the homogenization of lamina and laminate properties as well as the improved analytical calculation of spring-in for C-section and L-section composite parts. To validate the methodology, the lamina and laminate properties as well as the spring-in of symmetrical AS4/8552 C-section composite parts with cross-ply layers and HexPly®M18/1 L-section composite parts with multiple orthotropic layers are predicted and compared with the available measured data as the illustrative cases. The results show that the calculated lamina and laminate properties match well with the available measured values, with a maximum difference of 14.6%. And the analytically predicted spring-in angles of C-section and L-section parts agree well with experimentally measured data, with difference of 11.1% and 6.9% respectively. Graphical abstract: Image 1 Highlights: A simple methodology for predicting spring-in of curved composite parts is proposed. Homogenization of lamina and equivalent laminate properties is presented. The analytical solutions for spring-in of C-section and L-section composite parts is developed.